Online scenario simulation teaching in airway management for undergraduate anesthesia students - Lin, Yun; Wang, Ting-ting; Hou, Yuan-yuan; Lu, Xin-yu; Gao, Le-jun; Hersi, Salad Abdirahman; Gao, Peng; Wen, Qing-ping (Frontiers in Medicine, 2025)
BackgroundThe rapid growth of online education has led to the extensive exploration of innovative teaching methods to improve learning outcomes in medical training. This study aimed to evaluate the effectiveness of online scenario-based simulation in an airway management course for undergraduate anesthesia students.MethodsA total of 130 undergraduate students participated in an online airway management course. The primary objective was to assess the effectiveness of this teaching method by comparing post-class quiz scores. Secondary outcomes were evaluated based on technical and non-technical skills scores across four simulation scenarios. An anonymous questionnaire was also distributed to gather students’ perceptions and experiences.ResultsThe simulation group exhibited a significant improvement in post-class quiz scores compared to the traditional group (p < 0.001). In the second simulation, students showed enhanced technical skills across all four scenarios (p = 0.030, p = 0.037, p = 0.028, p = 0.028, respectively), as well as improved non-technical skills, including task management, teamwork, communication, vigilance, crisis identification, decision-making, and self-confidence. Questionnaire responses indicated that students found the course both enjoyable and beneficial in improving their problem-solving abilities. Additionally, 97.3% of participants felt the course enhanced their self-learning and teamwork skills, while 97.22% reported it facilitated mastery of anesthesia techniques.ConclusionOnline scenario-based simulation teaching has proven to be a highly effective and engaging educational tool for undergraduate anesthesia students. It significantly improves both technical and non-technical skills while promoting critical thinking and problem-solving development.